International-legal standards of cooperation of Ukraine in the field of environmental (climate) problems - Павлова, Юлія Сергіївна; Павлова, Ю. С.; Павлова, Юлия Сергеевна; Pavlova, Yuliia S.; Полуніна, Ольга Олександрівна; Полуніна, О. О.; Полунина, Ольга Александровна; Polunina, Olha O.; Ткалич, Максим Олегович; Ткалич, М. О.; Tkalych, Maxym О.; Маньковський, Володимир Валерійович; et al. (Universidad de la Amazonia, 2020)
Climate change because of global warming is one of the major and serious contemporary environmental problems that humanity has encountered. It is global climate change that causes the glaciers to melt, which increases the level of the global ocean and can cause the disappearance of some lands or even whole countries. Ukraine, like other countries, feels the consequences of climate change, as natural disasters such as floods, storm winds, and extreme temperatures are becoming more and more frequent. Natural disasters could be a reason for forest fires and other negative effects on the environment.Thus, the subject of the study is ways and measures of states on the issue of solving environmental problems and international legal regulation in this field.The object of the study is national and international legal acts on environmental issues.The methodology of research is formed by a set of general scientific and special methods of scientific knowledge. According to the results of the study, following conclusions were drawn; global warming is one of the most serious threatsto humanity, and to address this threat, it is necessary to unite States’ activities that have been achieved within the United Nations when the United Nations Framework Convention on Climate Change was adopted and the annual conferences of the parties were held, that resulted in adoption of the Kyoto Protocol in 1997, and the Agreement in 2015. For today, Ukraine is also actively cooperating with the EU in the framework of the Eastern Partnership Program on the process of harmonization of Ukrainian legislation in the field of environmental law and rules governing emergency situations.

Зміна клімату внаслідок глобального потепління є однією з гострих сучасних екологічних проблем, з якою зустрілося людство. Саме глобальна зміна клімату є причиною танення льодовиків, що, в свою чергу, збільшує рівень світового океану і може стати причиною зникнення земель і навіть держав в цілому. Україна, як і інші держави, гостро відчуває наслідки змін кліматичних умов, внаслідок чого стають частішими природні катастрофи, такі як повені, штормові вітри, екстремальні температури, які є однією з причин лісових пожеж та інших негативних наслідків для екології. Таким чином, предметом дослідження є шляхи та заходи держав щодо питання вирішення екологічних проблем та міжнародно-правового регулювання в цій сфері. Об’єктом дослідження є національні та міжнародні правові акти щодо питання вирішення екологічних проблем. Методологією дослідження є сукупність загальнонаукових та спеціальних методів наукового пізнання. За результатами проведеного дослідження були зроблені висновки, що глобальне потепління на сьогоднішній день є однією з найсерйозніших загроз для людства, і для боротьби з цією загрозою необхідне об'єднання діяльності держав, яке вдалося досягти в рамках ООН при прийнятті Рамкової конвенції ООН про зміну клімату та щорічних конференцій сторін, на яких були прийняті Кіотський протокол 1997 року та Паризька угода 2015 року. Сьогодні, Україна активно співпрацює разом із ЄС у рамках Програми східного партнерства над процесом гармонізації українського законодавства в галузі екологічного права та норм, які регулюють питання протидії надзвичайним ситуаціям.

Изменение климата в результате глобального потепления является одной из острых экологических проблем, с которой встретилось человечество. Именно глобальное изменение климата является причиной таяния ледников, что, в свою очередь, увеличивает уровень мирового океана и может стать причиной исчезновения земель и даже государств в целом. Украина, как и другие государства, остро ощущает последствия изменений климатических условий, в результате чего становятся более частыми природные катастрофы, такие как наводнения, штормовые ветры, экстремальные температуры, которые являются одной из причин лесных пожаров и других негативных последствий для экологии. Таким образом, предметом исследования являются пути и меры государств по вопросу решения экологических проблем и международно-правового регулирования в этой сфере. Объектом исследования являются национальные и международные правовые акты по вопросу решения экологических проблем. Методологией исследования является совокупность общенаучных и специальных методов научного познания. По результатам проведенного исследования были сделаны выводы, что глобальное потепление на сегодняшний день является одной из самых серьезных угроз для человечества, и для борьбы с этой угрозой необходимо объединение деятельности государств, которое удалось достичь в рамках ООН при принятии Рамочной конвенции ООН об изменении климата и ежегодных конференций сторон, на которых были приняты Киотский протокол 1997 г. и Парижское соглашение 2015 года. Сегодня, Украина активно сотрудничает вместе с ЕС в рамках Программы восточного партнерства над процессом гармонизации украинского законодательства в области экологического права и норм, регулирующих вопросы противодействия чрезвычайным ситуациям.
Pavlova Y. International-legal standards of cooperation of Ukraine in the field of environmental (сlimate) problems / Y. Pavlova, O. Polunina, M. Tkalych, V. Mankovskyi, A. Zubair // Amazonia Investiga. – V. 9 (25). – Universidad de la Amazonia, 2020. – P. 295-301.
Keywords: International legal standards; climate issues; environmental problems; emergencies; climate change; international cooperation; environmental threats; global warming; міжнародно-правові стандарти; кліматичні проблеми; екологічні проблеми; надзвичайні ситуації; зміна клімату; міжнародне співробітництво; загроза екології; глобальне потепління; международно-правовые стандарты; климатические проблемы; экологические проблемы; чрезвычайные ситуации; изменение климата; международное сотрудничество; угроза экологии; глобальное потепление; Research Subject Categories::LAW/JURISPRUDENCE